Serious Games Development and Applications 4th International Conference, SGDA 2013, Trondheim, Norway, September 25-27, 2013, Proceedings - Ma, Minhua; Fradinho Oliveira, Manuel; Petersen, Sobah; Baalsrud Hauge, Jannicke (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2013)
This book constitutes the refereed proceedings of the 4th International Conference on Serious Games Development and Applications, SGDA 2013, held in Trondheim, Norway, in September 2013. The 32 papers (23 full papers, 9 short papers/posters and 2 invited keynotes) presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections on games for health, games for education and training, games for other purposes, game design and theories, gaming interface, policy matters.